2022
DOI: 10.3389/fbioe.2022.894100
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Application of Carbon Dots With Synergistic Antibacterial Activity

Abstract: The diversity of bacteria and their ability to acquire drug resistance lead to many challenges in traditional antibacterial methods. Photothermal therapies that convert light energy into localized physical heat to kill target microorganisms do not induce resistance and provide an alternative for antibacterial treatment. However, many photothermal materials cannot specifically target bacteria, which can lead to thermal damage to normal tissues, thus seriously affecting their biological applications. Here, we de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 38 publications
1
22
0
Order By: Relevance
“…A simple and facile one-pot synthesis of the fluorescent CDs from orange waste peels was performed using the hydrothermal carbonization method at a mild temperature (180 °C). Likewise, in the present study, the biogenic synthesis of the CDs in the aqueous system results in a lesser yield, as mentioned in the results Section 3.1 , i.e., 83 mg per 1 g equating to nearly 8%, however, is more economical than other organic solvents like PEG (polyethylene glycol) used in the synthesis of CDs reported earlier in several studies [ 23 , 32 , 35 , 61 , 68 ]. The QY analysis demonstrated a lesser QY, that might be an attribute of larger CDs and a broad size distribution.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…A simple and facile one-pot synthesis of the fluorescent CDs from orange waste peels was performed using the hydrothermal carbonization method at a mild temperature (180 °C). Likewise, in the present study, the biogenic synthesis of the CDs in the aqueous system results in a lesser yield, as mentioned in the results Section 3.1 , i.e., 83 mg per 1 g equating to nearly 8%, however, is more economical than other organic solvents like PEG (polyethylene glycol) used in the synthesis of CDs reported earlier in several studies [ 23 , 32 , 35 , 61 , 68 ]. The QY analysis demonstrated a lesser QY, that might be an attribute of larger CDs and a broad size distribution.…”
Section: Discussionsupporting
confidence: 61%
“…The presence of N-H stretches, and bends was confirmed in the FT-IR spectrum. Other reported studies on the quantum yield of the CDs derived from various precursors showed a vast range of QY from 7.8% [ 45 ] to 85% [ 23 , 46 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At a small dose, it can effectively kill most E. coli and S. aureus within 5 min (Robby et al, 2021). Qie et al (2022) functionalized CQD with chiral biomolecules to prepare a bacterial affinity photothermal carbon point (BAPYCDs) for MurD ligase, and combined 808 nm 1.5 W cm −2 NIR laser with BAPYCDs. In 10 min, the BAPYCDs temperature of 200 μg ml −1 can be raised to 70.3 °C.…”
Section: Carbon Quantum Dotsmentioning
confidence: 99%